Transcatheter Arterial Embolization in Postpartum Hemorrhage: A Case Report - Alka Chhabra; Alka Chhabra; Anil Bhiwal; Neha Pandey; Sitaram Barath; Sunanda Gupta (Research and Practice in Anesthesiology, 2019)
Background Postpartum haemorrhage is the leading cause of maternal mortality and morbidity. The significant impact of postpartum haemor rhage (PPH) on maternal mortality can be reduced if timely measures are implemented. Transcatheter arterial embolisation (TAE) is an alternative therapeutic strategy for PPH. Case report We report a case of postpartum haemorrhage which was managed by transcatheter arterial embolization in lieu of hysterectomy to preserve fertility and menstruation in a 27-year-old patient. Conclusion The critical role of obstetrician, anaesthesiologist and interventional radiologist as a team, improve the quality of care and patient safety.